2018
DOI: 10.1155/2018/5214376
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Hemostatic Parameters in the Prediction for Type 2 Diabetes Mellitus and Diabetic Nephropathy

Abstract: It would be important to predict type 2 diabetes mellitus (T2DM) and diabetic nephropathy (DN). This study was aimed at evaluating the predicting significance of hemostatic parameters for T2DM and DN. Plasma coagulation and hematologic parameters before treatment were measured in 297 T2DM patients. The risk factors and their predicting power were evaluated. T2DM patients without complications exhibited significantly different activated partial thromboplastin time (aPTT), platelet (PLT), and D-dimer (D-D) level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 23 publications
5
21
0
Order By: Relevance
“…Also, Elevated WBC count even within the normal range has been reportedly associated with micro and macrovascular complications. 48,49 Evidence from epidemiological studies suggests an association between the WBC count, a non-specific marker of inflammation, and diabetes risk. 50 A significant negative correlation was found between neutro- production of cytokines may lead to inappropriate activation and tissue damage and even increase vulnerability to invasive microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Elevated WBC count even within the normal range has been reportedly associated with micro and macrovascular complications. 48,49 Evidence from epidemiological studies suggests an association between the WBC count, a non-specific marker of inflammation, and diabetes risk. 50 A significant negative correlation was found between neutro- production of cytokines may lead to inappropriate activation and tissue damage and even increase vulnerability to invasive microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, plasma fibrinogen is important in the regulation of inflammatory response 15 , and plasma fibrinogen levels are associated with increased inflammation 10 . Our previous studies have revealed that plasma fibrinogen is a powerful predictor for diabetic nephropathy in patients with T2D 16 , and combined plasma fibrinogen concentrations and MLR (FC-MLR) can be used as a powerful prognostic index of ovarian cancer 18 . Therefore, fibrinogen may play a combined role with MLR in inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that some changes of hemorheology would occurred in DM, especially PLT parameters, which leads to pathological changes of blood vessels. [10,11,34,35] As 2 important parameters of platelet, PDW and PLT attracted researchers’ attention and different opinions about whether they differ between patients and healthy controls were proposed. Thus, we systematically reviewed and summarized through a meta-analysis to explore the relationship between platelet parameters and DR, for identifying biomarkers for early detection of diabetic complications.…”
Section: Discussionmentioning
confidence: 99%
“…[10] And PLT also was reported to be an independent risk factor for type 2 diabetic mellitus (T2DM) and diabetic nephropathy. [11]…”
Section: Introductionmentioning
confidence: 99%